2018
DOI: 10.1002/fsn3.798
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of undernutrition among underfive children in Arusha District, Tanzania

Abstract: Childhood undernutrition is a global health challenge impacting child growth and survival rates. This deficit in nutritional status contributes to the increasing chronic disease prevalence and economic burden in individuals and throughout developing contexts. A community‐based cross‐sectional study was conducted in Arusha District of Tanzania to determine the prevalence and predictors of undernutrition in 436 children. A structured questionnaire was used to collect data on demographic and socio‐economic factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
9
15
0
Order By: Relevance
“…Children in the youngest age group of 0-6 months had a signi cantly lower risk of failure than in older age groups of above 6 months. These results are consistent with many other studies from other countries [15,24] as well as in Tanzania [2,22,23]. This may be because of either poor feeding practice of the older children, or sometimes vulnerability to diseases when a child grows from 6 months onwards.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Children in the youngest age group of 0-6 months had a signi cantly lower risk of failure than in older age groups of above 6 months. These results are consistent with many other studies from other countries [15,24] as well as in Tanzania [2,22,23]. This may be because of either poor feeding practice of the older children, or sometimes vulnerability to diseases when a child grows from 6 months onwards.…”
Section: Discussionsupporting
confidence: 92%
“…According to the UNICEF conceptual framework [21], undernutrition can be caused by insu cient diet intake, infections, poor breastfeeding or inadequate complementary foods. To date, numerous studies have been conducted to examine the determinants of undernutrition in Tanzania [2,[22][23][24] and elsewhere [15,17,[25][26][27]. However, available studies in the country have used conventional indices, rather than aggregated indicator of CIAF.…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of the studies (n = 10 studies) was conducted in urban settings, [24][25][26][27][28][29][30][31][32][33] and four studies were conducted in rural settings only. [34][35][36][37] One study was conducted in a periurban 38 and one study in a semi-rural setting. 39 The remaining six studies recruited participants from both rural and urban settings.…”
Section: A) Study Participants and Geographical Settingmentioning
confidence: 99%
“…[40][41][42][43][44][45] Overall, the studies selected for inclusion (n = 22 studies) involved a total of 26 609 participants, 12 453 (46.8%) participants were males, and one study recruited only women of reproductive age living in informal settlements in Accra, Ghana 29 . The distribution of the rest of the studies by countries was as follows: 4 from Ethiopia, 25,27,40,41 ; 1 Nigeria, 24 ; 1 Madagascar, 26 ; 3 Ghana, 29,38,39 ; 1 Zambia, 37 ; 2 Tanzania, 28,35 ; 1 Malawi, 34 ; 1 Cameroon, 33 ; 2 Sudan, 30,31 ; 1 Burkina Faso, 42 ; 1 Kenya, 32 ; 1 Botswana, 45 and 3 studies from South Africa 36,43,44 . Figure 2 shows the study distribution from the four regions of sub-Saharan Africa, with only 1 study from Central Africa 33 and…”
Section: A) Study Participants and Geographical Settingmentioning
confidence: 99%
“…The magnitude of wasting is substantial and persistent in the Sub-Saharan Africa [5] including Tanzania, where by a lot of children are suffering from the effects of acute malnutrition [6]. Different studies in Tanzania reported a high prevalence of wasting among children of under-five years [7][8][9]. The 2015 Tanzania Demographic and Health Survey report showed that wasting was more common in Zanzibar Island than in Tanzania Mainland (7% versus 4%).…”
Section: Introductionmentioning
confidence: 99%